PENCEGAHAN PENGGUNAAN NAPZA DAN PENANGANANNYA PADA KALANGAN REMAJA - Roushandy Fardani; Jihadil Qudsi; Ida Ayu Bulan K; M. Husaini Rosid (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Cases of drug abuse Narcotics, Psychotropics and Addictive are increasing rapidly in Indonesia, even though the government and society have made various efforts. Drug abuse is difficult to eradicate. What can be done is to prevent and control that problem does not spread, thereby harming the future of nation, due to the decline ini the quality of human resorces, especially younger generation. This counseling aims to provide information so that the younger generation clearly understands whats meant of drugs and understands the impacts of drug use. This activity use the extension method which was carried out at MA Ikhlasiyah Perampuan West Lombok, which was attended by 25 students. The result of this activity is that students can find out the types of drugs, what are the dangerous of using drugs that are abused, what are the disadvantages of abusing drugs. This can be seen from the participation who were able to answer during discussions and asking questions so that they are understood what the dangerous of drugs that could undermine and threaten their future if misused.